Markers of Central Neuropathic Pain in Higuchi Fractal Analysis of EEG Signals From People With Spinal Cord Injury - Anderson, Keri; Chirion, Cristian; Fraser, Matthew; Purcell, Mariel; Stein, Sebastian; Vuckovic, Aleksandra (Frontiers in Neuroscience, 2021)
Central neuropathic pain (CNP) negatively impacts the quality of life in a large proportion of people with spinal cord injury (SCI). With no cure at present, it is crucial to improve our understanding of how CNP manifests, to develop diagnostic biomarkers for drug development, and to explore prognostic biomarkers for personalised therapy. Previous work has found early evidence of diagnostic and prognostic markers analysing Electroencephalogram (EEG) oscillatory features. In this paper we explore whether nonlinear non-oscillatory EEG features, specifically Higuchi Fractal Dimension (HFD), can be used as prognostic biomarkers to increase the repertoire of available analyses on the EEG of people with subacute SCI, where having both linear and nonlinear features for classifying pain may ultimately lead to higher classification accuracy and an intrinsically transferable classifier. We focus on EEG recorded during imagined movement because of the known relation between the motor cortex over-activity and CNP. Analyses were performed on two existing datasets. The first dataset consists of EEG recordings from able-bodied participants, participants with chronic SCI and chronic CNP, and participants with chronic SCI and no CNP. We tested for statistically significant differences in HFD across all pairs of groups, and found significant differences between all pairs of groups at multiple electrode locations. The second dataset consists of EEG recordings from participants with subacute SCI and no CNP, some of whom had developed CNP before a followed-up 6 months later. We tested for statistically significant differences in HFD between those that had developed CNP within 6 months and those that did not, and, encouragingly, also found significant differences at multiple electrode locations. Transferable machine learning classifiers achieved over $80%$ accuracy discriminating between groups of participants with chronic SCI based on only a single EEG channel as input. The most significant finding is that future and chronic CNP share common features and as a result, the same classifier can be used for both. This sheds new light on pain chronification by showing that frontal areas, involved in the affective aspects of pain and believed to be influenced by long-standing pain, are affected in a much earlier phase of pain development.